# Closed form of $\sum_{n=1}^{\infty} \left(\frac{H_n}{n}\right)^4$

Find the closed form of $$\sum_{n=1}^{\infty} \left(\frac{H_n}{n}\right)^4$$

I know the closed form for smaller powers like $$2, 3$$ exists, but I'm not sure if there is a
closed form for this variant. Is it possible to tackle the question in an elementary way
and find the answer, without using integrals at all?

Then, if this exists, I'd also propose the alternating variant

$$\sum_{n=1}^{\infty} (-1)^{n+1} \left(\frac{H_n}{n}\right)^4$$

Update (by editor): The last sum by OP is: $$\small \sum _{n=1}^{\infty } (-1)^{n-1} \left(\frac{H_n}{n}\right){}^4=\frac{633}{128} \zeta(6,2)-\frac{1}{6} \pi ^2\zeta(\bar5,1)+6 \zeta(\bar7,1)-4 \zeta(\bar5,1,\bar1,1)+6 \log ^2(2) \zeta(\bar5,1)+12 \log (2) \zeta(\bar5,1,1)-16 \text{Li}_5\left(\frac{1}{2}\right) \zeta (3)-\frac{1}{9} \pi ^4 \text{Li}_4\left(\frac{1}{2}\right)+\frac{\pi ^2 \zeta (3)^2}{8}-\frac{63 \zeta (3) \zeta (5)}{64}+\frac{2}{15} \zeta (3) \log ^5(2)-\frac{2}{9} \pi ^2 \zeta (3) \log ^3(2)-\frac{31}{12} \zeta (5) \log ^3(2)+3 \zeta (3)^2 \log ^2(2)-\frac{16}{45} \pi ^4 \zeta (3) \log (2)-\frac{65}{48} \pi ^2 \zeta (5) \log (2)+\frac{155}{8} \zeta (7) \log (2)+\frac{149141 \pi ^8}{43545600}-\frac{1}{216} \pi ^4 \log ^4(2)+\frac{25 \pi ^6 \log ^2(2)}{1512}$$

• I know that $$\sum_{n=1}^{\infty} \left(\frac{H_n}{n}\right)^2 = \frac{17}{4} \zeta(4).$$ Could you give us the expression for the $3$ case? By the way related paper. Oct 27, 2014 at 22:31
• @user153012 $$\sum_{n=1}^{\infty} \left(\frac{H_n}{n}\right)^3=\frac{31}{5040}\pi^6-\frac{5}{2}\zeta^2(3)=\frac{93}{16}\zeta(6)-\frac{5}{2}\zeta^2(3)$$ Oct 27, 2014 at 22:45
• There is no closed form for the first Euler sum $s_h(4,4)$, but all weight-8 Euler sums can be expressed using zeta products and just one weight-8 Euler sum, whether it's $s_h(4,4)$ or $s_h(2,6)$ or some other one. Similarly for alternating Euler sums: there are four linearly independent alternating Euler sums necessary for a basis. (All this is conjectured.) Oct 29, 2014 at 13:21

The result is \begin{align*} S_{1^4,4}=\sum\limits_{n = 1}^\infty {\frac{{H_n^4}}{{{n^4}}}} = \frac{{13559}}{{144}}\zeta \left( 8 \right) - 92\zeta \left( 3 \right)\zeta \left( 5 \right) - 2\zeta \left( 2 \right){\zeta ^2}\left( 3 \right) + 26{S_{2,6}}, \end{align*} Detailed process see the paper Multiple zeta values and Euler sum" enter link description here

• What exactly is $S_{a,~b}$ ? Apr 5, 2017 at 15:14
• The $S_{p,q}$ denotes the linear Euler sum or double zeta value defined by Apr 5, 2017 at 23:00
• The $S_{p,q}$ denotes the linear Euler sum or double zeta value defined by$$S_{p,q}:=\sum\limits_{n = 1}^\infty {\frac{{H_n^{\left( p \right)}}} {{{n^q}}}},$$ where $p,q$ are positive integers with $q \geq 2$, and $w:=p+q$ denotes the weight of linear sums $S_{p,q}$. Apr 5, 2017 at 23:02
• $$\small \sum _{n=1}^{\infty } \left(\frac{H_n}{n}\right)^5=\frac{5}{6} \pi ^2 \zeta(6,2)+\frac{1365}{32} \zeta(8,2)+\frac{43 \pi ^4 \zeta (3)^2}{72}-\frac{35}{6} \pi ^2 \zeta (5) \zeta (3)-\frac{3215 \zeta (7) \zeta (3)}{16}-\frac{1997 \zeta (5)^2}{16}+\frac{31 \pi ^{10}}{7920}$$ Sep 3, 2020 at 13:43

First I'll simplify $\displaystyle S={ \left( \sum _{ m=1 }^{ n }{ \frac { 1 }{ m } } \right) }^{ 4 }$

Now, we can re-write it as: $$S=\left( \sum _{ { m }_{ 1 }=1 }^{ n }{ \frac { 1 }{ { m }_{ 1 } } } \right) \left( \sum _{ { m }_{ 2 }=1 }^{ n }{ \frac { 1 }{ { m }_{ 2 } } } \right) \left( \sum _{ { m }_{ 3 }=1 }^{ n }{ \frac { 1 }{ { m }_{ 3 } } } \right) \left( \sum _{ { m }_{ 4 }=1 }^{ n }{ \frac { 1 }{ { m }_{ 4 } } } \right)$$

This satisfies quasi-shuffle identity. So I can re-write it as:

$\displaystyle S=\left[ \underbrace{\left( \sum _{ n\ge { m }_{ 1 }>{ m }_{ 2 }>{ m }_{ 3 }>{ m }_{ 4 }>1 }^{ }{ + } \sum _{ n\ge { m }_{ 2 }>{ m }_{ 1 }>{ m }_{ 3 }>{ m }_{ 4 }>1 }^{ }{ + } \cdots \right)}_{24 \ terms} +\underbrace{\left( \sum _{ n\ge { m }_{ 1 }>{ m }_{ 2 }>{ m }_{ 3 }={ m }_{ 4 }>1 }^{ }{ + } \sum _{ n\ge { m }_{ 2 }>{ m }_{ 1 }>{ m }_{ 3 }={ m }_{ 4 }>1 }^{ }{ + } \sum _{ n\ge { m }_{ 1 }>{ m }_{ 3 }>{ m }_{ 2 }={ m }_{ 4 }>1 }^{ }{ + } ... \right)}_{12 \ terms} +\underbrace{\left( \sum _{ n\ge { m }_{ 1 }>{ m }_{ 2 }={ m }_{ 3 }>{ m }_{ 4 }>1 }^{ }{ + } \sum _{ n\ge { m }_{ 2 }>{ m }_{ 1 }={ m }_{ 3 }>{ m }_{ 4 }>1 }^{ }{ + } \sum _{ n\ge { m }_{ 1 }>{ m }_{ 4 }={ m }_{ 2 }>{ m }_{ 4 }>1 }^{ }{ + } \cdots \right)}_{12 \ terms} +\underbrace{\left( \sum _{ n\ge { m }_{ 1 }={ m }_{ 2 }>{ m }_{ 3 }>{ m }_{ 4 }>1 }^{ }{ + } \sum _{ n\ge { m }_{ 2 }={ m }_{ 3 }>{ m }_{ 1 }>{ m }_{ 4 }>1 }^{ }{ + } \sum _{ n\ge { m }_{ 1 }={ m }_{ 4 }>{ m }_{ 2 }>{ m }_{ 3 }>1 }^{ }{ + } \cdots \right)}_{12 \ terms} +\underbrace{\left( \sum _{ n\ge { m }_{ 1 }={ m }_{ 2 }={ m }_{ 3 }>{ m }_{ 4 }>1 }^{ }{ + } \sum _{ n\ge { m }_{ 1 }={ m }_{ 4 }={ m }_{ 2 }>{ m }_{ 4 }>1 }^{ }{ + } \cdots \right)}_{4 \ terms} +\underbrace{\left( \sum _{ n\ge { m }_{ 1 }>{ m }_{ 2 }={ m }_{ 3 }={ m }_{ 4 }>1 }^{ }{ + } \sum _{ n\ge { m }_{ 2 }>{ m }_{ 4 }={ m }_{ 1 }={ m }_{ 3 }>1 }^{ }{ + } \cdots \right)}_{4 \ terms} +\sum _{ n\ge { m }_{ 1 }={ m }_{ 2 }={ m }_{ 3 }={ m }_{ 4 }>1 }^{ }{ } \right] \frac { 1 }{ { m }_{ 1 }{ m }_{ 2 }{ m }_{ 3 }{ m }_{ 4 } }$

Now, on exploiting symmetry and using multi-harmonic sum I'll re-write it as: $$S=24{ H }_{ n }\left( 1,1,1,1 \right) +12{ H }_{ n }\left( 1,1,2 \right) +12{ H }_{ n }\left( 1,2,1 \right) +12{ H }_{ n }\left( 2,1,1 \right) +4{ H }_{ n }\left( 1,3 \right) +4{ H }_{ n }\left( 3,1 \right) +{ H }_{ n }\left( 4 \right)$$

Now, coming back to the problem. I'll insert the value of $S$ here.

$\displaystyle A=\sum _{ n=1 }^{ \infty }{ \frac { 24{ H }_{ n }\left( 1,1,1,1 \right) +12{ H }_{ n }\left( 1,1,2 \right) +12{ H }_{ n }\left( 1,2,1 \right) +12{ H }_{ n }\left( 2,1,1 \right) +4{ H }_{ n }\left( 1,3 \right) +4{ H }_{ n }\left( 3,1 \right) +{ H }_{ n }\left( 4 \right) }{ { n }^{ 4 } } }$

Now, I'll use the relation of multi-harmonic sum and multi-zeta variable: $$\sum_{n=1}^\infty \frac{H_n(s_1,\ldots,s_k)}{n^s}=\zeta(s,s_1,\ldots,s_k)+\zeta(s+s_1,s_2,\ldots,s_k).$$

$\boxed{A=24\zeta \left( 4,1,1,1,1 \right) +24\zeta \left( 5,1,1,1 \right) +12\zeta \left( 4,1,1,2 \right) +12\zeta \left( 5,1,2 \right) +12\zeta \left( 4,1,2,1 \right) +12\zeta \left( 5,2,1 \right) +12\zeta \left( 4,2,1,1 \right) +12\zeta \left( 6,1,1 \right) +4\zeta \left( 4,1,3 \right) +4\zeta \left( 5,3 \right) +4\zeta \left( 4,3,1 \right) +4\zeta \left( 7,1 \right) +\zeta \left( 4,4 \right) +\zeta \left( 8 \right) }$